PERSEPSI MASYARAKAT VERSUS PEMERINTAH TERHADAP LAYAK GUNA AIR: STUDI KASUS KALI JAGIR KELURAHAN NGAGELREJO SURABAYA - Sarkawi B. Husain (Jurnal Masyarakat dan Budaya, 2014)
Jagir River is one of the three important rivers in Surabaya, which provides the basic need of clean water for the citizens of Surabaya and its surroundings. However, the water has low quality, proved by the limp, dead, and floating fish on the river. In fact, some people still use it for their daily lives, from washing their clothes, bathing, defecating, to ablution. The question is why those people are still willing to use the poor water there for their daily needs. Does not the government perceive it as being polluted with various wastes? Using an ethnoecological approach, this paper aims to discuss the different perceptions between the government and the society about the river as well as the water quality of Jagir River. For the government, this river has two functions, namely (1) to divide and to control the water volume of Mas River in order to prevent the flood in Surabaya; and (2) to provide water for Perusahaan Daerah Air Minum/Regional Company for Drinking Water (PDAM) Surabaya in order to be produced as drinking water. Meanwhile, for those living in the riverside, Jagir River has four patterns of usage. Those are (1) spraying and watering, (2) cleaning, (3) performing ablution, and (4) taking recreation and earning a living. Keywords: perception, society, government, worthy-usable, water, Kali Jagir